High-Density Lipoprotein Subclasses, Coronary Artery Disease, and Cardiovascular Mortality. (1st December 2017) - Silbernagel, Günther; Pagel, Philipp; Pfahlert, Volker; Genser, Bernd; Scharnagl, Hubert; Kleber, Marcus E; Delgado, Graciela; Ohrui, Haruna; Ritsch, Andreas; Grammer, Tanja B; Koenig, Wolfgang; März, Winfried
Abstract: BACKGROUND: The inverse relationship between HDL cholesterol and cardiovascular mortality is weakened in coronary artery disease (CAD). We aimed to investigate the associations of HDL particle concentrations with cardiovascular mortality and the impact of CAD on these associations. We also sought to comparatively evaluate HDL cholesterol and HDL particle concentrations in predicting cardiovascular mortality. METHODS: Total and subclass HDL particle concentrations were measured by nuclear magnetic resonance spectroscopy in 2290 participants of the LUdwigshafen RIsk and Cardiovascular Health study referred for coronary angiography. The participants were prospectively followed over a median (interquartile range) duration of 10.0 (6.1–10.6) years. RESULTS: The mean (SD) age of the participants (1575 males, 715 females) was 62.9 (10.4) years; body mass index, 27.6 (4.1) kg/m 2 ; HDL cholesterol, 39 (11) mg/dL [1 (0.29) mmol/L]; and total HDL particle concentration, 24.1 (5.8) μmol/L. Of the participants, 434 died from cardiovascular diseases. In multivariate analyses, tertiles of total HDL particle concentrations were inversely related to cardiovascular mortality (hazard ratio for third vs first tertile = 0.55, P < 0.001). This association was primarily mediated by small HDL particles ( P < 0.001). Adding total or small HDL particle concentrations rather than HDL cholesterol to multivariate prediction models improved performance metrics for cardiovascular mortality. The presence of CAD had no impact on the associations between HDL particle concentrations and cardiovascular mortality. CONCLUSIONS: High HDL particle concentration is consistently and independently of CAD associated with decreased cardiovascular mortality. Whether the inverse relationship between HDL particle concentration and cardiovascular mortality may be translated into novel therapies is under investigation.